2021
DOI: 10.3389/fimmu.2021.649020
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Regulates the Immunosuppressive Effects of Myeloid-Derived Suppressor Cells in Tumor-Bearing Host

Abstract: Myeloid-derived suppressor cells (MDSCs) are immature heterogeneous cells derived from the bone marrow and they are the major component of the tumor-induced immunosuppressive environment. Tumor necrosis factor receptor-associated factor 6 (TRAF6), an E3 ubiquitin ligase, catalyzes the polyubiquitination of target proteins. TRAF6 plays a critical role in modulating the immune system. However, whether TRAF6 is involved in the regulation of MDSCs has not been thoroughly elucidated to date. In this study, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Depletion of RNF43 E3 ligase remodeled the TIME and facilitated Kras-induced oncogenesis in pancreatic cancer ( 110 ). TRAF6 E3 ligase reshaped TME by increasing the immunosuppressive functions of MDSCs via targeting K63-linked ubiquitination and phosphorylation of STAT3 ( 111 ). Knockdown of E3 ubiquitin ligase Cbl-b increased CAR T-cell effects and blocked CD8+ T-cell exhaustion, upregulated the expression of IFN-γ and TNFα, and accelerated tumor cell killing ( 112 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Depletion of RNF43 E3 ligase remodeled the TIME and facilitated Kras-induced oncogenesis in pancreatic cancer ( 110 ). TRAF6 E3 ligase reshaped TME by increasing the immunosuppressive functions of MDSCs via targeting K63-linked ubiquitination and phosphorylation of STAT3 ( 111 ). Knockdown of E3 ubiquitin ligase Cbl-b increased CAR T-cell effects and blocked CD8+ T-cell exhaustion, upregulated the expression of IFN-γ and TNFα, and accelerated tumor cell killing ( 112 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Nrdp1 mediates the ubiquitination of the transcription factor C/EBPβ at the K63 site, which promotes the activation of C/EBPβ and subsequently upregulates arginase 1 (Arg1) expression ( Ye et al, 2012 ). TRAF6 and arginase 1 are related, and they are expressed at high levels in myeloid-derived suppressor cells (MDSCs) ( Song et al, 2021 ). Ubc9-mediated SUMOylation of interferon regulatory factor 4 (IRF4) increases its nuclear localization and stability.…”
Section: Ubiquitination and Sumoylation In Amino Acid Metabolism In C...mentioning
confidence: 99%
“…Thus, TRAF6 plays a critical role in regulating the function of MDSCs. Song et al ( 134 ) reported that TRAF6 was highly expressed in the MDSCs of patients with lung cancer and TRAF6 knockdown impaired the immunosuppressive effects of MDSCs in vitro and in Lewis xenograft mice.…”
Section: Roles Of Ubiquitination In Modulating the Crosstalk Between ...mentioning
confidence: 99%